2006
DOI: 10.1111/j.1540-8183.2006.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale Using the Premere Device: The Results of the CLOSEUP Trial

Abstract: These data demonstrate that the Premere device can safely and effectively close PFO. Additional studies should be undertaken to demonstrate the effectiveness of PFO closure in reducing thrombo-embolic events such as stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…The BioSTAR septal repair implant used in the present study demonstrated closure rates superior to those reported previously with conventional synthetic devices 4,5,7 and is the first bioabsorbable device for the treatment of structural heart defects in humans.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The BioSTAR septal repair implant used in the present study demonstrated closure rates superior to those reported previously with conventional synthetic devices 4,5,7 and is the first bioabsorbable device for the treatment of structural heart defects in humans.…”
Section: Discussionmentioning
confidence: 44%
“…In the majority of cases, this can now be achieved by percutaneous transcatheter placement of a permanent synthetic implant to occlude the defect through a combination of mechanical closure and fibrous encapsulation of the device. [3][4][5][6] This process is not always fully achieved, and residual leaks are common after implantation. 4,5,7 In addition, late complications, including arrhythmia, 8 -11 erosions, [12][13][14] thrombus formation, 15 and allergic reactions, have been reported.…”
mentioning
confidence: 99%
“…Vast majority of the devices described in the ASD section, as and when they became available, were used to close PFOs. Existing ASD closure devices were modified or new devices designed to address the anatomic features of the foramen ovale and these include, Amplatzer PFO occluder [180], Cardia devices (PFO-Star and several of its subsequent generations) [172,181], Premere occluder [182], Occlutech septal occluder [183], Coherex Flat stent [184], pfm PFO-R [173], Solysafe PFO occluder [168] and others. Some of these devices are in clinical trials in and/or outside the US, and none are currently approved by FDA for general clinical use.…”
Section: Patent Foramen Ovalementioning
confidence: 99%
“…The sheath was withdrawn into the heart, and the patent foramen ovale closure device was placed through the guidewire as previously described for patent foramen ovale closure. 14 …”
Section: Transatrial Access With Closure Devicementioning
confidence: 99%